Complete mitochondrial genome of Eumeces elegans (Squamata: Scincidae). (2nd January 2016) - Song, Tao; Zhang, Chenling; Huang, Xin; Zhang, Baowei
Abstract: Eumeces elegans is a kind of blue-tailed lizard in the genus Eumeces, and widely distributed in southern provinces of China. We sequenced and characterized the complete mitochondrial genome of Eumeces elegans . The total length of the complete mitochondrial genome was 17, 304 bp with 13 protein-coding genes, 22 tRNAs, two rRNAs and a control regions. The overall base composition of Eumeces elegans was 31.0% A, 15.0% G, 29.8% C, and 24.2% T. ND6 subunit gene and eight tRNA genes were encoded on the L-stand, and other genes were distributed on the H-strand.